FORMULASI SEDIAAN GEL EKSTRAK ETANOL 96% RIMPANG JAHE MERAH (Zingiber officinale Rosc. Var. Rubrum) DENGAN HIDROKSIETIL SELULOSA SEBAGAI GELLING AGENT - L, Pricillya M; Falestin, Senny Listy Kartika; Julisna, Siska (Jurnal Riset Kefarmasian Indonesia, 2019)
Zingiber officinale Rosc. Var. Rubrum is a plant that has been determined to have antibacteria activity for Propionibacterium acnes which serve as one of the cause of acnes. Gel is the topical form used to acne’s medication. Hydroxiethyl Cellulose is used as gelling agent in gel of red ginger’s root’s ethanol 96% extract. The goal of the research is to determine the influence of increased concentration of hydroxiethyl cellulose to the formulation of red ginger’s root’s extract of ethanol 96%. The gel was made into 3 formulas with each concentration of 2%, 2.5%, and 3%. Each formulas wastested about the organoleptics, homogenity, pH, and viscosity. The result shows that on organoleptic test, the gels don’t have any change, they are homogen and their pH were stable. Based on the viscosity test, 1st, 2nd and 3rd formulas have some increase with the addition of storage’s time. The formula 1 have less viscocity with the concentration of about 2%. Based on this research, we can conclude that the 1 st formula was the best one based on the physical, chemical quality and the organoleptic test.